Effectiveness of Stunting Prevention Program In Cirebon Regency - Ferdiana Yanuar, Fedri; Ahmad Sudrajat, Faisal; Nursahidin, Nursahidin; Haryo Bharoto, R. Mahendra (Asian Journal of Social and Humanities, 2024)
This study aims to determine the effectiveness of stunting prevention programs in Cirebon Regency conducted by the Health Office. This program is based on rules and regulations regulated by local and central governments, and involves various stakeholders and available resources. A qualitative approach was used in this study, with a descriptive method to describe the phenomena that occur. Program effectiveness is evaluated based on Richard M. Steers' theory identifying three indicators of effectiveness, namely goal achievement, integration, and adaptation. The findings show that the program has made progress in reducing stunting, although there are still some challenges faced, such as lack of coordination and limited resources. Therefore, this study concludes that stunting prevention efforts need to be continuously improved by improving coordination between agencies, strengthening program integration, and adapting to changing environmental conditions.